Scalp angiosarcoma in elderly patient: case report - Oona S. Erdmann; Isabelle L. Lemos; Karina B. Medeiros; Juliana E. Jung; Eduardo M. de-Castro (Revista da Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Cutaneous angiosarcomas are rare, aggressive tumors, and represent < 1% of all malignant head and neck neoplasms. Their highest incidence is in elderly men and Caucasians. The importance of reporting cases of this type of tumor is to emphasize it as a differential diagnosis in the elderly. We report a 90-year-old Caucasian male patient with an erythematous and infiltrative scalp tumor. Surgical resection and anatomopathological evaluation, including immunohistochemical studies, diagnosed a high-grade angiosarcoma. Primary cutaneous angiosarcoma is the main form of angiosarcoma, with rapid evolution, affecting mainly the scalp and face. It presents with varied morphologies, irregular growth, and spontaneous bleeding. Microscopic findings include infiltrating and anastomosing vascular channels lined by atypical endothelial cells, as well as solid growth in high-grade tumors. The prognosis is poor, usually related to the patient’s age, lesion site, and disease stage. The variable microscopy may mimic other neoplasms, and a wide spectrum of diseases should be considered in the differential diagnosis.